Mathematical modeling of the impact of recirculation on exchange kinetics in tandem extracorporeal membrane oxygenation and therapeutic plasma exchange. Issue 1 (8th October 2020) - Puelz, Charles; Marinaro, Jonathan L.; Park, Yara A.; Griffith, Boyce E.; Peskin, Charles S.; Raval, Jay S.
Abstract: Vascular access connection configurations during tandem extracorporeal membrane oxygenation (ECMO) and therapeutic plasma exchange (TPE) may impact exchange kinetics. In these tandem procedures, typically the TPE inlet line is proximal to the TPE return line with respect to blood flow in the ECMO device, maximizing the opportunity for replacement fluid homogenization within the ECMO circuit. However, if TPE inlet and return line connections are switched, recirculation—a phenomenon in which replacement fluid leaving the TPE return line is prematurely drawn into the TPE inlet line prior to satisfactory homogenization within the ECMO circuit—will occur. Such recirculation could diminish TPE efficacy in patients on ECMO and mitigate therapeutic benefits. Using a mathematical model of recirculation in tandem ECMO and TPE, we demonstrate that the predicted impact of recirculation is negligible and vascular access connection positioning does not appear to be a point of clinical concern with regard to TPE kinetics.